Goal orientation and task demand effects on motivation, affect, and performance. - Steele-Johnson, Debra; Beauregard, Russell S.; Hoover, Paul B.; Schmidt, Aaron M. (Journal of Applied Psychology, 2000)
Two studies tested the joint effects of goal orientation and task demands on motivation, affect, and performance, examining different factors affecting task demands. In Study 1 (N = 199), task difficulty was found to moderate the effect of goal orientation on performance and affect (i.e., satisfaction with performance). In Study 2 (N = 189), task consistency was found to moderate the effect of goal orientation on self-efficacy and intrinsic motivation. Results are discussed in relation to self-regulatory processes cued by goal orientations, attentional resource demands, and the need to match goal orientations to the nature of the task.